СКРИНИНГ: СОВРЕМЕННЫЙ ВЗГЛЯД НА РАННЮЮ ДИАГНОСТИКУ И ПРОФИЛАКТИКУ ХРОНИЧЕСКИХ НЕИНФЕКЦИОННЫХ ЗАБОЛЕВАНИЙ - Ж. В. Максимова; Д. М. Максимов (Архивъ внутренней медицины, 2014)
The article is focused on the theoretical and practical aspects of screening — a modern method of secondary prevention and early detection of the most important chronic non-communicable diseases and their risk factors. The article describes screenings which benefits overwhelm potential harms: for smoking, alcohol abuse, obesity, hypertension, dyslipidemia, type 2 diabetes, osteoporosis, abdominal aortic aneurysm, cervical cancer, breast cancer, colon cancer and lung cancer.